Pengaruh Pendekatan Pembelajaran SAVI (Somatic, Auditory, Visual, Intellectual) terhadap Hasil Belajar Matematika Peserta Didik Materi Bangun Ruang Kelas IV SDN Randegan - Rokhmania, Adelina; Wijaya, Bagus Rahmat (Yayasan Arrahman Nahdlatul Wathan, 2024)
This study aimed to determine the effect of the SAVI learning approach (Somatic, Auditory, Visual, and Intellectual) on student's mathematics learning outcomes in three-dimensional materials for grade IV SDN Randegan. This study used quantitative methods with a one-group pretest-posttest design. The population of this study was all IV grade students of SDN Randegan in the school year of 2023/2024. The Sampling used in this study was a total sampling technique. The sample in this study consisted of 28 students. Data were collected using pretest and posttest questions, psychomotor assessment, and observation. The results of this study indicate that: 1.) the learning outcomes of students in the cognitive domain got a t-observed of -19.357 ≥ -1.701 and in the psychomotor domain obtained a t-observed of -17.860 ≥ -1.701 (negative signs only indicating the direction of hypothesis testing, not indicating the amount) which means there is a significant difference between pretest scores and posttest scores in each learning domain, 2). Because there is a significant difference between the pretest and posttest values in each learning domain, it can be concluded that there is an effect of the SAVI learning approach (Somatic, Auditory, Visual, and Intellectual) on student's mathematics learning outcomes in three-dimensional material for grade IV of SDN Randegan.